2012
DOI: 10.4103/0971-9261.93963
|View full text |Cite
|
Sign up to set email alerts
|

Chronic cervical lymphadenopathy in children: Role of ultrasonography

Abstract: Aim:To assess the usefulness of ultrasonography in the differentiation of causes of chronic cervical lymphadenopathy in children.Materials and Methods:Children with palpable cervical lymph nodes were included. An ultrasonographic examination was performed to delineate multiple lymph nodes, irregular margins, tendency towards fusion, internal echos, the presence of strong echoes and echogenic thin layer.Results:The total number of patients was 120. Echogenic thin layer and strong internal echoes were specific f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…20 Mild-looking cervical lymphadenopathy with no obvious aetiological cause should be monitored frequently for at least 2-4 weeks. 21 Caution should be exercised in excluding a diagnosis with fine-needle aspiration as it may not lead to a definitive diagnosis in detecting pathogens and malignancies in the presence of epithelioid cell granulomas and necrosis. 15 An excision biopsy, to obtain sufficient tissue, is the examination of choice to confirm the diagnosis in the case of a suspected malignancy, persistent lymphadenopathy or resistant to antibiotic treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Mild-looking cervical lymphadenopathy with no obvious aetiological cause should be monitored frequently for at least 2-4 weeks. 21 Caution should be exercised in excluding a diagnosis with fine-needle aspiration as it may not lead to a definitive diagnosis in detecting pathogens and malignancies in the presence of epithelioid cell granulomas and necrosis. 15 An excision biopsy, to obtain sufficient tissue, is the examination of choice to confirm the diagnosis in the case of a suspected malignancy, persistent lymphadenopathy or resistant to antibiotic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…20 Mild-looking cervical lymphadenopathy with no obvious aetiological cause should be monitored frequently for at least 2–4 weeks. 21…”
Section: Discussionmentioning
confidence: 99%
“…Although enlarged cervical lymph nodes are common in children, during the 1st 6 years of life, neuroblastoma and lymphoma are the most common tumors associated with cervical lymphadenopathy. [9] The role of US was to identify nodes suspected of malignancy, with the round shape and long axis to short axis ratio less than 2. [10] None of the enlarged lymph nodes in our study had such features and that is why all enlarged lymph nodes were diagnosed as benign lymphadenopathy.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Pandit A et al out of twenty cases of pyogenic lymphadenitis seven cases revealed tubercular lymphadenitis on subsequent histological examination 13 .…”
Section: Observationmentioning
confidence: 98%